The Role of Orthostatic Hypotension in the Development of Nocturia in Parkinson’s Disease - Košytė, Deimantė; Čičelienė, Jolita (Neurologijos seminarai, 2024)
Background. Parkinson‘s disease is a chronic neurodegenerative disorder where one of the most common non-motor symptoms is nocturnal urination, also known as nocturia. It can be caused by sleep disturbances, increased urine production and impaired urine storage. Disorders of the autonomic nervous system, such as orthostatic hypotension (OH), may also contribute to nocturia. The aim of this review article is to assess the association between nocturia and OH in PL and to discuss possible diagnostic and therapeutic approaches.Materials and methods. A non-systematic review of the scientific literature was performed. Publications were retrieved by PubMed search engine using keywords and their combinations The non-systematic literature review included publications published in 2016–2025.Results. Nocturia is one of the frequently occurring non-motor symptoms of Parkinson’s disease, significantly impairing patients’ sleep quality and overall well-being. Its causes are related to increased urine production and storage disorders; however, increasing attention is being directed toward autonomic nervous system dysfunctions, especially orthostatic hypotension. The accumulation of α-synuclein in the autonomic nervous system, characteristic of Parkinson’s disease, may be one of the contributing factors in the development of orthostatic hypotension. Orthostatic hypotension and the associated supine hypertension may worsen the manifestation of nocturia. Diagnosis requires careful medical history-taking, blood pressure monitoring during changes in body position, and laboratory tests. Treatment demands a comprehensive approach: lifestyle modifications, physical exercise, pharmacotherapy, and other methods, depending on the individual patient’s needs and the possible causes of nocturia.Conclusions. Orthostatic hypotension and other related conditions may play an important role in the manifestation of nocturia. For individuals with Parkinson’s disease, a personalized and thorough assessment of symptoms is essential, with particular attention to manifestations of autonomic nervous system dysfunction.
Keywords: Nocturia; Parkinson’s disease; orthostatic hypotension